2021
DOI: 10.1002/anie.202100261
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Tuning the Excited State Hückel–Baird Hybrid Aromatic Character of Pro‐Aromatic Quinoidal Compounds**

Abstract: The present study aims to provide a solid ground for the identification, characterization and controlled design of pro-aromatic quinoidal organic compounds holding conjugated rings with Hückel and/or Baird (singlet and triplet) excited state aromatic character, and expects to become a reference work for future studies on Baird-aromaticity. Concretely, we explore a wide range of compounds with a central conjugated ring of different sizes and symmetric exocyclic substitutions. We employ a combination of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…As Hückel-aromaticity implies a larger number of paired electrons in the aromatic cycle it should, when possible, be preferred over Baird-aromaticity. 41 Hence, care needs to be exercised and one needs to explore what type of aromaticity is at hand in a particular system when in its lowest triplet or singlet excited state. There is otherwise a clear risk of the overuse of the Baird-aromaticity concept to molecules to which it does not apply.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Hückel-aromaticity implies a larger number of paired electrons in the aromatic cycle it should, when possible, be preferred over Baird-aromaticity. 41 Hence, care needs to be exercised and one needs to explore what type of aromaticity is at hand in a particular system when in its lowest triplet or singlet excited state. There is otherwise a clear risk of the overuse of the Baird-aromaticity concept to molecules to which it does not apply.…”
Section: Discussionmentioning
confidence: 99%
“…Now, the value of DFLU ab /FLU claries whether a cycle is Baird-aromatic or Hückel-aromatic because DFLU ab is zero or negligible for a Hückel-aromatic cycle while it has a nonzero value for a Baird-aromatic cycle. 40,41 As references, indole and pyrrole in their closed-shell Hückel-aromatic S 0 states have DFLU ab /FLU values which are exactly zero while the Baird-aromatic indole and pyrrole dications in their triplet states have calculated values of 2.34 and 4.02, respectively (Table S1 †). We now nd that the DFLU ab /FLU ratios of the AB/A 0 B 0 moieties and the B/B 0 rings of T 1 state CIBA are low (À0.180 and À0.186, respectively), supporting an interpretation of the T 1 state in terms of Hückelaromaticity.…”
Section: Parent Cibalackrotmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Later the influence of Hückel aromaticity in the excited state was thoroughly investigated in the exo-substituted 1,6methano [10] annulene derivatives, establishing guidelines to tune Hückel/Baird aromaticity in the excited state. [9] Hückel aromaticity can be observed in both S 0 and in lowest excited states for certain polycyclic systems by discrete distribution of aromatic character between the rings. [10] For example, in the case of dipyrrolonaphthyridinedione derivatives adaptive aromatic character was claimed with Baird type excited state [5] in an earlier study and was later computationally shown to be of Hückel type.…”
Section: Introductionmentioning
confidence: 99%
“…Later the influence of Hückel aromaticity in the excited state was thoroughly investigated in the exo‐substituted 1,6‐methano [10] annulene derivatives, establishing guidelines to tune Hückel/Baird aromaticity in the excited state [9] . Hückel aromaticity can be observed in both S 0 and in lowest excited states for certain polycyclic systems by discrete distribution of aromatic character between the rings [10] .…”
Section: Introductionmentioning
confidence: 99%